การพัฒนาความสามารถในการอ่านออกเสียงตัวอักษรภาษาอังกฤษ /W/,/V/, และ /R/,/L/ โดยใช้แบบฝึกทักษะโฟนิกส์ (Phonics) สำหรับนักเรียนระดับมัธยมศึกษาปีที่ 3 - คลังตุ้ย, ภูตะวัน; วรบุตร, ถาวร; กรมน้อย, อานันท์; ไทยมิตร, แสงอาทิตย์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 3 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 3 : กันยายน - ธันวาคม 2567, 2024)
This research aims to: (1) develop the ability of Grade 9 students to pronounce the English sounds /W/, /V/, /R/, and /L/ using phonics-based exercises, ensuring that students meet an 80% performance criterion and that 80% of students meet or exceed this criterion; and (2) examine students' satisfaction with the development of their pronunciation skills for the English sounds /W/, /V/, /R/, and /L/ using phonics exercises. The target group consists of 31 Grade 9 students from Ban Phai Pittayakom School. This study employs an action research methodology. The research instruments include Action tools: 1.1) Three lesson plans, totaling 9 hours. Tools for reflecting on the actions are: 2.1) An assessment form for pronunciation ability at the end of three cycles, 2.2) Teacher’s instructional record, 2.3) Student behavior observation form. Tools for evaluating the effectiveness of learning activities are: 3.1) An evaluation form for pronunciation ability of the sound’s /W/, /V/, /R/, and /L/, 3.2) A satisfaction survey. Quantitative data analysis will involve calculating the mean (µ), standard deviation (σ), and percentage (%). Qualitative data will be analyzed using content analysis.               The research findings revealed that:               1) The students achieved an average score of 16.90, representing 84.51% of the total score, with 23 students meeting the criteria, accounting for 90.32% of all students—exceeding the set benchmark.               2) In terms of student satisfaction with the phonics exercises for pronouncing the English sounds /W/, /V/, /R/, and /L/, the Grade 9 students reported an average satisfaction score of 4.56, indicating a "very high" level of satisfaction.